2015
DOI: 10.1038/ncomms8058
|View full text |Cite
|
Sign up to set email alerts
|

Tie-mediated signal from apoptotic cells protects stem cells in Drosophila melanogaster

Abstract: Many types of normal and cancer stem cells are resistant to killing by genotoxins, but the mechanism for this resistance is poorly understood. Here we show that adult stem cells in Drosophila melanogaster germline and midgut are resistant to ionizing radiation (IR) or chemically induced apoptosis and dissect the mechanism for this protection. We find that upon IR the receptor tyrosine kinase Tie/Tie-2 is activated, leading to the upregulation of microRNA bantam that represses FOXO-mediated transcription of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
77
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(90 citation statements)
references
References 58 publications
11
77
1
Order By: Relevance
“…Although aged stem cells have been shown to accumulate DNA damage, it remains largely unclear how DNA damage affects stem cell self-renewal and differentiation. A previous study has reported that upon weak irradiation apoptotic differentiated GSC progeny can prevent GSC loss by activating Tie-2 receptor tyrosine kinase signaling (Xing et al, 2015). In this study, we show that temporally introduced DNA double-stranded breaks cause premature GSC loss and slow down GSC progeny differentiation (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Although aged stem cells have been shown to accumulate DNA damage, it remains largely unclear how DNA damage affects stem cell self-renewal and differentiation. A previous study has reported that upon weak irradiation apoptotic differentiated GSC progeny can prevent GSC loss by activating Tie-2 receptor tyrosine kinase signaling (Xing et al, 2015). In this study, we show that temporally introduced DNA double-stranded breaks cause premature GSC loss and slow down GSC progeny differentiation (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Random lasers123 (RLs) are a special class of lasers with Lévy-type distributions of intensity fluctuations45678910111213, which has been recently exploited as a photonic platform for studies of complex systems, such as spin glasses141516171819202122. RLs were originally proposed23 by Letokhov in the late 1960’s, but their first unambiguous observation was only reported in 1994 by Lawandy and collaborators24.…”
mentioning
confidence: 99%
“…In the photonic context, the term spin glass (SG) means that intensity spectra emitted under identical experimental conditions keep a complex pattern of correlations1516171819202122, as quantified below. Moreover, the Lévy statistics implies strong fluctuations in the emission intensity, with non-Gaussian heavy-tailed distribution45678910111213.…”
mentioning
confidence: 99%
“…It has been previously reported that dividing germline cystocytes undergo a Caspase-dependent cell death in response to metabolic stresses (Drummond-Barbosa and Ikeya et al, 2002;Morrison and Spradling, 2008). Activated Caspase labeling of GSCs was surprising, however, given that it has been reported that GSCs and other stem cells are resistant to apoptosis after irradiation (Xing et al, 2015). It is possible that mitochondrial stress is a more potent inducer of apoptosis in stem cells than the genotoxic stress caused by irradiation.…”
Section: Discussionmentioning
confidence: 99%